THE INFLUENCE OF INSTAGRAM’S PICTURES TOWARDS THE STUDENTS’ ESSAY WRITING SKILL - Destia Herlisya; Riska Alfiawati; Irvan Dodo (JETA (Journal of English Teaching and Applied Linguistic), 2020)
This research reports on the effectiveness of Instagram’s pictures towards the students’ essay writing skill. Instagram becomes one of the famous social media in the world, in this research Instagram is used as a medium to improve the students’ essay writing skill. The aims of the research were to know and to describe student’s essay writing skill and to know and to describe whether there is influence of Instagram’s pictures towards student’s essay writing skill. The research was conducted by using a quasi-experimental design with pretest and post-test. The population of this research are the students at the sixth semester of English education major at STKIP PGRI Bandar Lampung, that consisted of 76 students in 2 classes. The sample of this research were two classes, they were as control class and experimental class. Control class was taught by Individual writing while experimental class was taught by Instagram’s pictures. In getting the data, the writer used writing test. The result showed that based on the calculation, the writer got that = 5.92 and = 1.67 and 2.39. It means that . So, Ho is rejected and Ha is accepted.From the result above, the writer states that there is a positiveinfluence of Instagram’s pictures towards students’ essay writing skill.